El Miʾyār de al-Wanšarīsī (m. 914/1508). II:Contenido - Vidal Castro, Francisco (Miscelánea de Estudios Árabes y Hebraicos. Sección Árabe-Islam, 2013)
This paper is the second part of a study about the great collection of legal response (fatwàs) issued in al-Andalus and North Africa of al-WanšarIsI (m. 914/1508): al-Mi`yar al-mu`rib wa-l- yami` al-mugrib `an fatawà `ulama' Ifriqiya wa-l-Andalus wal-Magrib. The present article focuses on the aspects of the contents: objective of the work, subjects, structure, methodology for the use and exploitation, résumé of the contents for each volumen, the muftis, labour of the author, summaries of the work, posterior influence and general valuation.